2021
DOI: 10.1002/jgc4.1407
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Genetic Diagnosis of a Sex Chromosome Aneuploidy: Parent Experiences

Abstract: The use of cell-free DNA (cfDNA) screening has increased the prenatal detection of fetal chromosome anomalies, including sex chromosome aneuploidies (SCAs). Collectively, SCAs are the most common chromosomal condition among live births, with an estimated prevalence of 1 out of 300-400 births (Bojesen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 52 publications
1
35
0
Order By: Relevance
“…Whether identified prenatally or postnatally, a diagnosis of XYY can be difficult for families to process. For many families, the diagnosis comes as a surprise, as most parents report not having prior knowledge of SCA at the time of diagnosis (Riggan et al 2020(Riggan et al , 2021. Thus, receiving a diagnosis of XYY can present as a traumatic event and often lead to feelings of grief, distress, and guilt (Lalatta et al 2012;Riggan et al 2021).…”
Section: Individual and Family Experiences Of The Diagnostic Journeymentioning
confidence: 99%
See 2 more Smart Citations
“…Whether identified prenatally or postnatally, a diagnosis of XYY can be difficult for families to process. For many families, the diagnosis comes as a surprise, as most parents report not having prior knowledge of SCA at the time of diagnosis (Riggan et al 2020(Riggan et al , 2021. Thus, receiving a diagnosis of XYY can present as a traumatic event and often lead to feelings of grief, distress, and guilt (Lalatta et al 2012;Riggan et al 2021).…”
Section: Individual and Family Experiences Of The Diagnostic Journeymentioning
confidence: 99%
“…While it is common for families to experience feelings of worry and uncertainty, some families, especially those with children diagnosed postnatally, may feel relieved after receiving a diagnosis (Riggan et al 2020(Riggan et al , 2022. Conversely, parents who receive a prenatal diagnosis are at an increased risk of feeling depressed, anxious, and less optimistic (Jaramillo et al 2019;Riggan et al 2020Riggan et al , 2021.…”
Section: Individual and Family Experiences Of The Diagnostic Journeymentioning
confidence: 99%
See 1 more Smart Citation
“…Prior qualitative research with parents of children with SCAs has mostly focused on the diagnostic experience and medical care, where parents have reported a desire for more supportive delivery of the diagnosis as well as more holistic and optimistic presentation of SCAs from medical professionals (Jaramillo et al, 2019;Riggan et al, 2021). Richardson et al (2021) found parents of children with SCAs are often forced to assume the roles of 'expert' and 'advocate' as they navigate the multiple systems in which their children interact, including the educational, medical and social support systems.…”
Section: Parent Perspectivesmentioning
confidence: 99%
“…Prior qualitative research with parents of children with SCAs has mostly focused on the diagnostic experience and medical care, where parents have reported a desire for more supportive delivery of the diagnosis as well as more holistic and optimistic presentation of SCAs from medical professionals (Jaramillo et al., 2019; Riggan et al., 2021). Richardson et al.…”
Section: Introductionmentioning
confidence: 99%